Rhetorical Audience Studies and Reception of Rhetoric Exploring Audiences Empirically (Rhetoric, Politics and Society, 2018)
This book examines the reception of rhetoric and the rhetoric of reception. By considering salient rhetorical traits of rhetorical utterances and texts seen in context, and relating this to different kinds of reception and/or audience use and negotiation, the authors explore the connections between rhetoric and reception. In our time, new media and new forms of communication make it harder to distinguish between speaker and audience. The active involvement of users and audiences is more important than ever before. This project is based on the premise that rhetorical research should reconsider the understanding, conceptualization and examination of the rhetorical audience. From mostly understanding audiences as theoretical constructions that are examined textually and speculatively, the contributors give more attention to empirical explorations of actual audiences and users. The book will provide readers with new knowledge on the workings of rhetoric as well as illustrative and guiding examples of new methods of rhetorical studies.